3D CBCT human adult odontometrics: Comparative assessment in Saudi, Jordan and Egypt population - Mohammad Khursheed Alam; Bader K Alzarea; Kiran Kumar Ganji; Ibadullah Kundi; Santosh Patil (Elsevier, 2019)
Objectives: To inspect the human adult odontometrics by the assistance of 3D cone beam computerized tomography (CBCT) imaging in Saudi, Jordan and Egypt population. Materials and Methods: Data of this cross sectional study from 252 subject were analysed by 3D CBCT volumetric data in college of dentistry, Aljouf University, from December 2016 to May 2017. All measurements were done by 3D on demand software. The tooth size from 2nd molar to 2nd molar of maxillary and mandibular arch was measured. Independent t test and ANOVA were used to examine the differences between gender and among Arabic population (Saudi, Jordan and Egypt) on the all tooth size. Results: Comparison between the right and left side odontometrics were significantly dissimilar in 9 out of 14 pairs (p < 0.05). The odontometrics of the 2nd molar to 2nd molar tooth of maxillary and mandibular arch between gender and among Saudi, Jordan and Egypt population were insignificant (p > 0.05). Conclusion: 3D CBCT imaging permits us to measure the tooth size effectively and accurately. Based on results, significant asymmetry was revealed in 9 out of 14 pairs in relation to side disparities. No significant differences in tooth size between gender and among races were found. CBCT can elevate the record keeping problem, human adult odontometrics for the analysis can be obtained directly from the digital image. Keywords: 3D CBCT, Odontometry, Sexual dimorphism, Asymmetry